Generative AI text summarization performance analysis prospects - Tsypliak, Oleksandr; Artemchuk, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
AI investment world trends analysis in scope based on venture investments timeline by domain visualization and researches proves that not all AI-agent development projects are successful. The current paper describes an AI-agent performance analysis approach based on LLM-specific metrics and scenario-specific metrics. The AI-agent for highlights generation is in focus as an object of performance analysis.